(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-76-84 Abstract. In this article, features of structural and semantic-pragmatic transformation of ritual in the text of a fairy tale are under the analysis. Ritual is interpreted as a complex cultural sign, the expression plane of which is represented by a fixed scenario of successive actions, the content plane - by the values of the cultural community, used for the purposes of cultural designing. The main research method is discourse analysis, which includes the study of the content and communicative intentions of text fragments. The study develops the idea that a ritual can lose its characteristics and properties and transform them into a quasi-ritual. Russian fairy tales indirectly reflect rituals that have been developed in the culture. These actions are represented in the folklore text in a contracted, indexed form as some hints of rituals. To identify quasi-rituals, the article suggests considering the following factors: the action is attributed to a sacred meaning, it has a regular character, and it is aimed at achieving some result by the characters. While examining the selected object, it has been established that ritual practices are conventional, their performance is attributed with a sacred meaning. Ritual actions represent a complex idiomatic sign and are perceived as a whole; quasi-ritual actions are perceived by the naive consciousness as ordinary actions participating in the construction of a narrative. The storyteller draws readymade narrative programs from the cultural-cognitive base, which are perceived as sacred actions attributed to the characters of the fairy tale. The meaning of quasi-ritual actions is dominated by the subject component, that is, the state of affairs indicated by the sign, intentions, in comparison with the correlating ritual, changes completely. The quasi-ritual changes its significate. The ritual is aimed at changing and constructing reality, and the quasi-ritual is informative. Quasi-rituals have an archetypal basis: their cultural etymons reflect person’s naive ideas about the surrounding reality, which means that quasi-rituals indirectly reflect cultural norms. If a functional classification is more suitable for rituals, then a denotative classification is more suitable for quasi-rituals. Key words: language, culture, cultural sign, ritual, quasi-ritual, fairy tale